Neural discriminability in rat lateral extrastriate cortex and deep but not superficial primary visual cortex correlates with shape discriminability - Vermaercke, Ben; Van den Bergh, Gert; Gerich, Florian; Op de Beeck, Hans (Frontiers in Neural Circuits, 2015)
Recent studies have revealed a surprising degree of functional specialization in rodent visual cortex. It is unknown to what degree this functional organization is related to the well-known hierarchical organization of the visual system in primates. We designed a study in rats that targets one of the hallmarks of the hierarchical object vision pathway in primates: selectivity for behaviorally relevant dimensions. We compared behavioral performance in a visual water maze with neural discriminability in five visual cortical areas. We tested behavioral discrimination in two independent batches of six rats using six pairs of shapes used previously to probe shape selectivity in monkey cortex (Lehky and Sereno, 2007). The relative difficulty (error rate) of shape pairs was strongly correlated between the two batches, indicating that some shape pairs were more difficult to discriminate than others. Then, we recorded in naive rats from five visual areas from primary visual cortex (V1) over areas LM, LI, LL, up to lateral occipito-temporal cortex (TO). Shape selectivity in the upper layers of V1, where the information enters cortex, correlated mostly with physical stimulus dissimilarity and not with behavioral performance. In contrast, neural discriminability in lower layers of all areas was strongly correlated with behavioral performance. These findings, in combination with the results from Vermaercke et al 2014, suggest that the functional specialization in rodent lateral visual cortex reflects a processing hierarchy resulting in the emergence of complex selectivity for behaviorally relevant stimulus differences.